Evaluating optic nerve diameter as a possible biomarker for disability in patients with multiple sclerosis - Koraysha NA (Dove Medical Press, 2019)
Noha Abo Koraysha,1 Nirmeen Kishk,1 Amr Hassan,1 Nehal M Samy El Gendy,2 Hatem S Shehata,1 Salsabil Abo Al-Azayem,1 Yasmine Shawki Kamal1 1Neurology Department, Kasr Al Ainy Hospital, Cairo University, Cairo, Egypt; 2Ophthalomology Department, Kasr Al Ainy Hospital, Cairo University, Cairo, EgyptCorrespondence: Nehal M Samy El GendyOphthalomology Department, Kasr Al Ainy Hospital, Cairo University, 43th Gameat El Dewal Street, Cairo 12411, EgyptTel +20 100 108 5164Email Nehal.ElGendy@kasralainy.edu.egBackground and purpose: The development of new biomarkers for multiple sclerosis (MS) is of paramount importance to improve our ability to predict disease progression and disability. The aim of this study was to evaluate the potential role of the optic nerve diameter (OND) measured by ultrasonography as a biomarker of early disability in patients with relapsing-remitting multiple sclerosis (RRMS).Methods: Forty-nine RRMS patients, 23 with a history of optic neuritis (MS-ON) and 26 without a history of optic neuritis (MS N-ON), and 50 age- and sex-matched healthy control subjects were included in the study. The OND and optic nerve sheath diameter (ONSD) were measured by transorbital sonography (TOS), and the retinal nerve fibre layer (RNFL) and ganglion cell complex (GCC) thicknesses were measured by optical coherence tomography (OCT) using the Optovue RTVue™ system (Optovue, Inc., Fremont, CA, USA).Results: There was no significant difference between the patient (whether ON or N-ON eyes) and control groups in either the OND (p=0.979) or the ONSD (p=0.911). However, patients with an expanded disability status scale (EDSS) score >2 had a significantly lower OND and RNFL thicknesses (p=0.014, p=0.010 respectively) than patients with an EDSS score ≤2. Statistical logistic regression revealed that OND was an independent predictor of EDSS>2 (p=0.044, OR =0.000, 95% CI=0.000–0.589).Conclusion: The OND, as measured by ultrasonography, could be potentially used as a biomarker for the detection of early disability in RRMS patients.Keywords: multiple sclerosis, biomarker, OCT, transorbital sonography, RNFL